Optimalisasi Peran Masyarakat dalam Pengolahan Daun Strawberry - Farhan Fakhruddinsyah; M. Jundi Abdillah; Aulia A. Putri Putri; Ade Iskandar Nasution (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
This community service activity was motivated by the suboptimal utilization of strawberry leaf waste in Sugihmukti Village, which has so far focused only on the fruit. However, strawberry leaves have the potential to be used as raw material for economically valuable herbal products. This activity aims to increase the community's knowledge and skills in processing strawberry leaf waste into herbal tea. The method used is the Asset-Based Community Development (ABCD) approach through the stages of observation, planning, outreach, workshops, direct practice, and evaluation. The activity involved lecturers, KKN students, and the local community, especially women from the Family Welfare Movement (PKK). The results of the activity showed that the community was able to understand the process of herbal tea processing and had basic skills in producing it independently. In addition, this activity also increased community awareness of utilizing local potential and opened up business opportunities based on herbal products.the program.